Associating genetic variation at Perilipin 1, Complement Factor D and Adiponectin loci to the bone health status in North Indian population - Sandhu, Harkirat Singh; Puri, Sanjeev; Sharma, Rubina; Sokhi, Jasmine; Singh, Gagandeep; Matharoo, Kawaljit; Bhanwer, AJS (Gene, 2017)
Osteoporosis, the most common bone metabolic disease affecting nearly 200 million people worldwide is under the strong influence of genetic components. Simultaneously, adipogenesis and osteogenesis are two highly coordinated processes imperative for the maintenance of bone quality and quantity, where any perturbation leads to pathological conditions of obesity, osteopenia and osteoporosis. To delineate this adipogenic-osteogenic connection, a total of 254 cases (T-score<−1.0 SD) and 250 age, gender and ethnicity matched healthy controls (T-score≥−1.0 SD) were recruited from North India after analyzing bone health status employing quantitative ultrasound (QUS) bone densitometer. The genetic variants of Perilipin 1 (PLIN1), Complement Factor D (CFD) and Adiponectin (ADIPOQ) were genotyped using the PCR-RFLP/ARMS-PCR approach. Subjects with CC+CT (PLIN1 rs2304795) and CC+CG (CFD rs1683563) genotypes conferred nearly 1.54–1.87 fold increased risk towards bone deterioration. Predicted RNA secondary structures of rs2304795 corroborated the risk associated with wild type C allele. G allele carriers at the ADIPOQ locus (rs1501299) were more likely to have a lower bone health (1.57-fold). Haplotype analysis revealed the ADIPOQ variants rs1501299 and rs3774261 in slight linkage disequilibrium (LD), nonetheless G/G haplotype was associated with increased risk. 3-locus and 5-locus gene-gene interaction models revealed a greater likelihood of bone deterioration. In conclusion, certain variants of adipogenic genes might serve as potential biomarkers for determining the genetic predisposition towards bone loss in the North Indian population, further, emphasizing the role of impaired metabolism in bone health. •Genetic variants of adipogenic markers PLIN1, CFD and ADIPOQ confered increased susceptibility towards low bone mass.•G/G haplotype of ADIPOQ (rs1501299 and rs3774261) exhibited increased risk.•3-locus and 5-locus gene-gene interaction models revealed greater likelihood of low bone mass.•Predicted RNA secondary structures substantiated risk associated with PLIN1 rs2304795.•Relationship between impaired metabolism and bone health is established.